Assessment of parent/ caretaker satisfaction with child and adolescent mental health services in a tertiary care setting - Mahpara Mazhar , Faisal Rashid Khan , Asad Tamizuddin Nizami , Sadia Yasir (Journal of Rawalpindi Medical College, 2021)
BACKGROUND: Assessment of parent/caretaker satisfaction with child and adolescent mental health services in a tertiary care setting METHODS: In this descriptive cross sectional study, 130 parents/caretakers of children aged ≤ 16 years were administered Parent/Caretaker Satisfaction Questionnaire which is a 20-item, 4-point Likert type scale, after their second visit/consultation with Child Psychiatric OPD via non-probability consecutive sampling directly as well as telephonically during six months period. Demographic variables were collected via Proforma. The data was analyzed using SPSS v 16.0. p- value <0.05 was considered significant. RESULTS: 73.1% (n=95) were very satisfied (satisfaction level>60), 24.6 %(n=32) were satisfied (satisfaction between 21-60) and only 2.3%(n=3) were unsatisfied (satisfaction ≤20). No significant association was found between demographic variables and level of satisfaction. CONCLUSION: Our study revealed a high level of parent/caretaker satisfaction with Child and Adolescent mental health services in a tertiary care setting. No significant association was found between socio-demographic variables and parent/caretakers’ satisfaction. KEY WORDS: Patient satisfaction, Quality of health care, Child Psychiatry, Mental health services